Explore EFL Learners Vocabulary Learning Strategies - Rahmatika, Annisa; Pertiwi, Dian; Karmala, Estiana Tri; Nastiti, Intan Aulia (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This research is aimed at exploring vocabulary learning strategies used by EFL students. This research will try to explore vocabulary strategies used by EFL students in the range between 16 18 years old. 44 students with the same ability of English are used as the subject of this research. This is a naturalistic research. The data for this research is collected by using questionnaire. Data were analyzed using simple descriptive percentage calculations. The questionnaire was written in Indonesian which is consisted of 30 statements. Those statements are grouped under 9 categories. Those nine categories are adapted from Gu and Johnson vocabulary learning strategies. Thus, the research questions are: 1) what strategies are used the most by the EFL learners? 2) what strategies are used the least by the EFL learners? The result of this research are the strategies most often used by the EFL learners in this study were memorization (in terms of social strategies) and dictionary strategies, while the least used strategy discovered is note taking strategies.